? How has Dubai Become a World – Renowned Megacity - Alhajji, Zakiah Radhi (Journal of natural sciences, life and applied sciences, 2017)
Megacities are large urban centers with populations in excess of 10 million inhabitants. Today Dubai is coming in at 1st place as the world’s most developed and emerging world location, it tops Hong Kong and Copenhagen, ranking 3rd for its Economic Potential and 8th for Connectivity and Business Friendliness. These are the qualities that class Dubai as the Middle East’s “2025 Hot Spot for Future Competitive Cities” (Economist Intelligence), as well as being the 7th most influential city in the world. Yet Dubai has only been anointed this status in its recent history. Its population has been expanding dramatically only as recently as 2005, with a surge of 25% in that year alone. The scope of this review is limited to resources that have been published both online and in print in the English language. Primarily these are works of scholars educated in the West, published in the last ten years. This review will not explore the works of Emirati scholars written in their native language of Arabic, nor any sources prior to 2002. This is because the growth of Dubai and the relevant subsequent analysis has occurred mostly in the past decade. Its relevance to the West is of key importance to its growth, hence English publications have been chosen. For the time being, Dubai’s current status as megacity remains contested. Its population is roughly nine times smaller than the defined population size of a megacity, yet some critics insist on its megacity status given Dubai’s global presence and publicity. Megacities are defined by a population of at least ten million inhabitants.